WOMEN'S FOOTBALL ASSOCIATION. DEVELOPMENT OF WOMEN'S FOOTBALL - Amonturdiyev Bakhtiyor Kurbanovich (American Journals, 2023)
Women's association football, known simply as women's football, is a team sport of association football played exclusively by women. It is played professionally in many countries and has 176 international teams.
Keywords: National, association, FIFA, grounds, dominated, popular, beach soccer